Using Mobile-Based Formative Assessment in ESL/EFL Speaking - Mahedi Hasan; A B M Shafiqul Islam; Israt Jahan Shuchi (Journal of Languages and Language Teaching, 2021)
With the widespread application of smartphones in and outside the classroom, mobile-based teaching and learning is drawing much attention and hence being extensively practised nowadays across the globe. Recently, using smartphones for assessment purposes has been a new phenomenon and the researchers are still examining what processes the use of mobile-based assessment tools may include and what outcomes and challenges they can cause to teachers and students in terms of learning/teaching performance, motivation and attitudes. There have been a good number of research studies on the use of Mobile Assisted Language Learning (MALL) or Mobile Learning (ML) in EFL or ESL classroom but not much literature is known about the mobile-based language assessment, especially mobile-based formative assessment (MBFA). Hence, this study attempts to shed light on MBFA and review the recent literature available on it and its effective utilization in developing ESL/EFL speaking skill. This paper uses a qualitative research method that exclusively uses the relevant secondary references/works available on the topic. The literature revealed that MBFA practices in ESL/EFL speaking classes are effective to a certain extent and some tools and procedures seem to be more effective than others depending on the design principles and strategies used by teachers or app developers.